Node-Place Analysis Model s in the Development of Transit-Based Activity Nodes in Pangkalpinang City - Widyastuti, Dyah Titisari; jibril, Mohammad (Universitas Syiah Kuala, 2025)
Pangkalpinang City is the capital of Bangka Belitung Province, which has a strategic location as a transit city. Pangkalpinang City also has an important role as a center for offices, administration, economy, and transportation on Bangka Island. Pangkalpinang City's status as the capital of Bangka Belitung Islands Province, the center of regional activities, and the center of office, administration, economy, and transportation activities on Bangka Island. Therefore, the need for the development of activity nodes that synergize with public transportation is very important, because the current condition of Pangkalpinang City has public transportation but it is not the main choice. This research is a quantitative descriptive study using an empirical analytic approach based on Node-Place Model analysis to identify the conditions of activity nodes that occur and the balance between nodes (public transportation networks) and places (potential places for interaction and activity between humans) or land use activities. This is because the node-place model is a concept used to analyze and balance two important elements in urban development, namely nodes and places. This concept was developed to understand how the interaction between transportation systems and land use can affect population mobility and regional development. This study concludes that mobility patterns in Pangkalpinang City are centered around activity hubs, including office complexes, educational institutions, recreational areas, residential areas, and trade and service areas. The development typology focuses on increasing transit points, parking availability, pedestrian paths, population growth, and infrastructure improvements to support transit-oriented areas.